English Word Formation in Indonesian Film Titles - Rifina Fithrotunnisa; Sulistyowati (Universitas Islam Negeri Palopo, 2026)
This article aims to investigate English word-formation processes that found in Indonesian film titles. Although English is a foreign language in Indonesia, but it is widely used in daily communication. English is also used in naming of Indonesian film titles. Film titles are easily found in public spaces and social media, making them relevant for linguistic analysis. The analysis of word formation using the word-formation classification proposed by Bauer (1983). This study uses a descriptive qualitative method. The data are collected from the Internet Movie Database (IMDb) and FilmIndonesia.or.id. The researcher selects film titles that contain English elements and analyzes how the words are formed. The findings show several types of word-formation processes, including inflection, derivation, compounding, blending, acronym, and coinage. These processes indicate that English is used creatively in Indonesian film titles, especially in blending formation.